Funciones desempeñadas como asistente contable en la empresa Consorcio F&F Contratistas Generales S.A.C. - Espejo Moncada, Nadia Vanessa (2019)
This report entitled "FUNCTIONS PERFORMED AS AN ASSISTANT ACCOUNTANT AT THE COMPANY CONSORTIUM F & F CONTRATISTAS GENERALES SAC" is based on the experience obtained during the years 2012 - 2016, during which time I put into practice the knowledge obtained in my university education according to the curriculum of the Professional School of Accounting and Finance. This Professional Sufficiency Work was developed with the objective of applying Section 23: Revenue from Ordinary Activities of the IFRS for SMEs to construction contracts and determine their effect on the company's results. Determine the amount of accrued income and the treatment of customer advances according to Section 23, as well as the degree of termination, the result of a construction contract and, the treatment for the difference between the income according to the billing and the accrued income By applying the IFRS for SMEs in Section 23: Revenue from Ordinary Activities, we obtain results for the period based on reliable and Integra information, unlike the non-application of said section. Contributing to reliable financial information, which allows you to make appropriate decisions and accurately evaluate the management of the company's resources. According to the Income Tax Law, Article 63 (b), for construction contracts that exceed a taxable year, accrued income is determined according to the work performed in accordance with the provisions of Section 23 of the IFRS for SMEs. Also in its article 57 ° has defined the concept of accrued in accordance with IFRS.